Analisis Pengukuran Kinerja Anggaran pada Dinas PUPR Kota Bengkulu Ditinjau dari Perspektif Ekonomi Islam - Lisa Setia Nengsih; Eka Sriwahyuni; Rizky Hariyadi (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to determine the measurement of budget performance at the PUPR office of Bengkulu City reviewed from the aspect of Islamic economics. This study uses a combination method (mixed methods) / combination of quantitative-qualitative. The study was conducted at the PUPR Office of Bengkulu City, Jl. Soeprapto Dalam Simpang 4 Betungan, Bengkulu City. Data collection techniques used were observation, questionnaires, interviews and documentation. Finally, it was analyzed using the Value Of Money method and interview method. The results show that 1) Budget performance at the PUPR Office of Bengkulu City shows very positive achievements. The management of the 2023 budget for the implementation of road improvements has been carried out with the principles of economy, efficiency, and effectiveness, where the budget realization of 98.43% reflects the use of funds that are economical and on target. In addition, the level of effectiveness reaching 98.38% proves that the development program is able to meet the physical performance targets that have been set, thus providing real benefits for the welfare of the community. This achievement shows that the PUPR Office of Bengkulu City has managed the budget professionally with optimal results, in line with the principle of Value for Money. 2) Then from the perspective of Islamic Economics, the budget performance at the PUPR Office of Bengkulu City shows strong conformity with the principles of transparent, fair, and trustworthy financial management. Economical budget management, without waste (israf) or squandering (tabdzir), reflects the application of Islamic values ​​in ensuring that each fund is used proportionally and according to real needs.